The Absent Father: a Vietnamese folktale and its French shadows - Aveling, Harry (Penerbit Universiti Kebangsaan Malaysia, 2017)
This paper discusses some variants of a Vietnamese folktale that we shall generically call “The Shadow of the Absent Father”. The Emperor Le Thanh Tong first refers to the story in a poem written during the fifteenth century. The earliest detailed record of the tale, “The Story of the Woman from Nam Xuong”i by Nguyen Du (1496-1527)ii, is to be found in the sixteenth century volume Truyen Ky Man Luc (A Casually Recorded Collection of Popular Tales,)iii. There are many French language versions of the tale in collections of Vietnamese legends made throughout the twentieth century.iv. We will focus here on two by the scholar and diplomat Pham Duy Khiem (1908- 1974), which are included in his books Légendes des terres sereines (Legends from Serene Lands, 1942)v and La jeune femme de Nam Xuong (The Young Woman from Nam Xuong, 1944)vi respectively. They are told in very different ways. I will argue that “The Shadow and the Absent Man”, from the earlier volume, is more consistent in style and content with Khiem’s other writing. The latter, very traditional version, “The Young Woman from Nam Xuong”, represents a way of telling the tale that is alien to his style and outlook, thus leading it to be eventually excluded from the canon of Khiem’s work. I will also suggest that the story bears some of the dynamics of his own family experience.